Les députés islamistes algériens (2012-2017) : ce que le passage à l’opposition fait à « la modération » - Belkacem Benzenine (L’Année du Maghreb)
As of the 2012 Algerian legislative elections, the Islamist parties decide to leave the government and choose the rank of the opposition. Maintaining continuity with the line of moderation, Islamist MPs use the parliamentary space as a forum for challenging government action. Based on a corpus of debates in the Algerian National Assembly, this article shows how Islamist MPs operate to defend their political line while showing their commitment to the principle of moderation.